Exploring Quantum Capacitance and Adsorption Energy of Alkali Metal on NiO Using First‐Principles DFT Calculations - Sandesh V. Gaikwad; Pushpinder G. Bhatia; Digambar M. Sapkal; Deepak P. Dubal; Gaurav M. Lohar (Electron)
ABSTRACT This study presents an analysis of the structural, electronic, and surface properties of NiO using first‐principles density functional theory (DFT) calculations. The investigation focuses on three lattice parameters (a = 4.23 Å, 4.187 Å, and 4.183 Å) to explore how lattice strain influences the electronic band structure, density of states (DOS), quantum capacitance (QC), and adsorption energies of alkali metals (Li, Na, K) on the NiO [001] and [111] planes. The study reveals that a decrease in the lattice parameter leads to a reduction in the band gap (from 2.28 to 2.19 eV). The adsorption energies demonstrate a strong surface reactivity, with Li showing the highest affinity for the NiO [001] surface and Na exhibiting the highest adsorption energy on the more reactive NiO [111] surface. The QC analysis demonstrated notable enhancements following alkali metal adsorption, with Li on the NiO [001] surface exhibiting a QC of 38.9 μF/cm2 at a = 4.23 Å, whereas Na on the NiO [111] surface achieved a QC of 32.7 μF/cm2 at a = 4.187 Å. These findings underscore the critical role of lattice strain and surface orientation in modulating the electrochemical performance of NiO, with potential applications in catalysis, energy storage, and electronic devices.